2016
DOI: 10.1007/s10571-016-0409-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Ro25-6981 Against Ischemia/Reperfusion-Induced Brain Injury via Inhibition of Autophagy

Abstract: In this study, we investigated the neuroprotective effect of Ro25-6981 against cerebral ischemia/reperfusion injury. Ro25-6981 alone or in combination with rapamycin was intracerebroventricularly administered to rats which suffered transient forebrain ischemia inducing by 4-vessel occlusion and reperfusion. Nissl staining was used to determine the survival of CA1 pyramidal cells of the hippocampus, while immunohistochemistry was performed to measure neuron-specific enolase (NSE) expression. The expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…Currently, the role of autophagy in cerebral ischemic stroke is still inconclusive. Some studies indicate that autophagy is detrimental to neurons during cerebral ischemic injury and inhibiting autophagy can decrease the infarct size and augment neurological scores . However, other studies show that autophagy activation or enhancing mitophagy can protect against IR‐induced injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the role of autophagy in cerebral ischemic stroke is still inconclusive. Some studies indicate that autophagy is detrimental to neurons during cerebral ischemic injury and inhibiting autophagy can decrease the infarct size and augment neurological scores . However, other studies show that autophagy activation or enhancing mitophagy can protect against IR‐induced injury .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicate that autophagy is detrimental to neurons during cerebral ischemic injury and inhibiting autophagy can decrease the infarct size and augment neurological scores. 38,39 However, other studies show that autophagy activation or enhancing mitophagy can protect against IR-induced injury. 40 The present study added evidence that autophagy was significantly activated and was detrimental to neurons in the acute stage of ischemia injury.…”
Section: Discussionmentioning
confidence: 99%
“…The population of normal neurons in a CA1 subfield were counted at 400× magnification by 2 independent investigators who were blind to the experimental condition in this study. The mean number of neurons was obtained by counting 3 sections per brain and 5 representative fields were randomly selected to count per section (n=4/group) [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Autophagy is a highly regulated process involving the bulk degradation of cytoplasmic macromolecules and organelles in mammalian cells . Autophagy is involved in many pathophysiological situations, such as inflammation , apoptosis , malignancy , and cerebral ischemia/reperfusion injury .…”
mentioning
confidence: 99%
“… also found that ischemic preconditioning enhances autophagy but suppresses autophagic cell death in rat spinal neurons following ischemia/reperfusion, while other reports have found that inhibition of autophagy is protective against ischemia/reperfusion injury. An NMDA glutamate receptor antagonist, Ro25‐6981, suppresses ischemic brain injury by inhibiting autophagy . Inhibition of the mitochondrial calcium uniporter also protects neurocytes against ischemia/reperfusion injury by downregulating excessive mitophagy .…”
mentioning
confidence: 99%